2016
DOI: 10.1155/2016/4519201
|View full text |Cite
|
Sign up to set email alerts
|

Correct Definition of Sound Speed and Its Consequences in the Tasks of Hydrodynamics

Abstract: The paper considers the applied problems of hydrodynamics and based on the new results, published by the author in recent years, shows that main assumptions used in the course of their solution, namely, incompressibility of liquids and potentiality of their movement, are not applicable to liquids in the gravitational field of the Earth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Contradictions that are present in the theory of surface waves are described in detail in the works [16] and [19]. In this work, through the example of capillary waves we have explicitly investigated the causes of these contradictions and showed how to overcome them.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Contradictions that are present in the theory of surface waves are described in detail in the works [16] and [19]. In this work, through the example of capillary waves we have explicitly investigated the causes of these contradictions and showed how to overcome them.…”
Section: Resultsmentioning
confidence: 96%
“…This result was obtained under the assumption of the potentiality of motion and incompressibility of a fluid, on which the entire existing theory of gravitational waves is based [2]- [15]. In the work [16] it was shown that the movement of fluid in a gravitational field of the Earth cannot be potential. It was also shown that the condition of incompressibility is inapplicable to liquids, because it leads to the existence of an internal wave [1], the nature of which is completely inexplicable from the point of view of physics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the field of underwater communication began with the experiment of a physicist/engineer Jean-Daniel Colladon and a mathematician Charles-Francois Sturn in 1826. They obtained that the sound was transmitted in the water faster than in the air [2]. With the subsequent studies, this research area has become interesting, with the necessary knowledge base to examine underwater acoustic communication today.…”
mentioning
confidence: 99%